(untitled) (Bangladesh Journal of Medical Physics, 2019)
Analysing published experimental findings this paper revealed that for myelinated nerves the conduction velocity (CV) increases on stretching out of the nerve, which has not been pointed out by anyone before. This apparently contradicts existing concepts since stretching out of a nerve fibre reduces its diameter which is expected to reduce the CV. Besides, the change is reversible and immediate, which cannot be explained with existing knowledge either. In order to explain this anomaly, the present work invoked a new resistance to ion flow between the nerve axon and the extracellular fluid created by interdigitated fingerlike processes of myelin sheaths coming from two sides of a node of Ranvier, analyzing published electron microscopic images. When stretched out, the gaps between the processes increase, decreasing the resistance to ion flow and thereby hastening depolarization, increasing CV in turn. The gaps close immediately on the release of the stretching force because of the pull of the elastic endoneurium, thus retrieving the original CV. To represent this new mechanism, a new resistive element has been added to the existing electrical model of a myelinated nerve, which is being claimed to be the dominant component that determines the conduction delay. Stretching also affects other nerve parameters and this paper developed a mathematical formulation involving all these parameters to show satisfactorily that CV indeed increases with stretching, in which the contribution of the proposed resistance dominates. The paper also proposed an appropriate modification of the representative schematic model commonly used to depict propagation of action potential in a myelinated nerve fibre. The suggested new mechanism and the resistance model is a breakthrough in the explanation of neural conduction and opens up the door for new study as well as for reviewing all previous experiments on myelinated nerves afresh. Bangladesh Journal of Medical Physics Vol.11 No.1 2018 P 38-56